SALIVARY GLAND’s STEM CELLS - Chaіkovsky Yu.B.; Geraschenko, S.B.; Deltsova О.I. (World of Medicine and Biology, 2012)
The review of literature is devoted to modern views on possibilities of restoration of parenchyma and stroma in adults with the use of salivary gland stem cells. From the studied sources of literature follows, that exists possibility of regeneration of secretory cells in acinus. Salivary gland stem cells and cells- precursors are localized in the intercalated ducts, have their own stem niches and are characterized by specific features of identification.